Landsat sub-pixel land cover dynamics in the Brazilian Amazon - Souza, Carlos M.; Oliveira, Luis A.; de Souza Filho, Jailson S.; Ferreira, Bruno G.; Fonseca, Antônio V.; Siqueira, João V. (Frontiers in Forests and Global Change, 2023)
The Brazilian Amazon land cover changes rapidly due to anthropogenic and climate drivers. Deforestation and forest disturbances associated with logging and fires, combined with extreme droughts, warmer air, and surface temperature, have led this region to high tree mortality and harmful net carbon emissions. Regional attempts to characterize land cover dynamics in this region focused on one or two anthropogenic drivers (i.e., deforestation and forest degradation). Land cover studies have also used a limited temporal scale (i.e., 10-15 years), mainly on global and country-scale forest change. In this study, we propose a novel approach to characterize and measure land cover dynamics in the Amazon biome. First, we defined ten fundamental land cover classes: Forest, Flooded Forest, Shrubland, Natural Grassland, Pastureland, Cropland, Outcrop, Bare and Impervious, Wetland, and Water. Second, we mapped the land cover based on the compositional abundance of Landsat sub-pixel information that makes up these land cover classes: Green Vegetation (GV), Non-Photosynthetic Vegetation, Soil, and Shade. Third, we processed all Landsat scenes with less than 50% cloud cover. Then, we applied a step-wise random forest machine learning algorithm and empirical decision rules to classify intra-annual and annual land cover classes between 1985 and 2022. Finally, we estimated the yearly land cover changes in forested and non-forested ecosystems and characterized the major change drivers. In 2022, Forest covered 78.6% (331.9 Mha) of the Amazon biome, with 1.4% of secondary regrowth in more than five years. Total herbaceous covered 15.6% of the area, with the majority of Pastureland (13.5%) and the remaining Natural Grassland. Water was the third largest Land Cover class with 2.4%, followed by Cropland (1.2%) and Shrubland (0.4%), with 89% overall accuracy. Most of the Forest changes were driven by Pasture and Cropland conversion, and there are signs that climate change is the primary driver of the loss of aquatic ecosystems. Existing carbon emission models disregard the types of Land Cover changes presented in the studies. The 21st century requires a more encompassing and integrated approach to monitoring anthropogenic and climate changes in the Amazon biome for better mitigation, adaptation, and conservation policies.